Specialism - Blamey, David, 1961- (London, United Kingdom : Open Editions, 2016)
Blamey, David ; Cornford, Matthew ; Cummings, Neil ; Fox, Dan ; Grose, Anouchka ; Hu, Mingyuan ; Knott, Stephen ; Loeffler, Frances ; Power, Nina ; Poynor, Rick ; Rider, Alistair ; Robinson, Andrew ; Rogoff, Irit ; Sonderegger, Ruth ; Watson, Chris ; Woencroft, Jon ; Whittlesea, Ian
boek
Keywords: Art -- History; Specialism (Philosophy)